Socialization of Organic Waste Management as a Circular Economy Solution for Food Security and Sustainable Livestock Farming in Kupang City - Fernando Saragih; Aditya Pamungkas; Bella Theo Tomi Pamungkas (Pascasarjana Universitas Mataram, 2025)
Waste management remains a significant environmental challenge in Oesapa Barat Village, Kota Kupang, where proper handling systems and community awareness have not kept pace with the annual increase in waste volume. Low participation in waste sorting and the absence of structured waste utilization have contributed to environmental degradation. This community engagement program aimed to enhance public awareness and skills in managing organic waste through educational activities and hands-on training. The program was delivered using presentations, group discussions, demonstrations, and direct practice on transforming organic waste into compost and maggot feed as part of a circular economy model. The results indicate a significant improvement in participants' understanding of waste impacts, the benefits of organic recycling, and the economic opportunities from maggot cultivation. Approximately 70% of participants expressed willingness to apply simple waste-processing techniques at home. These findings suggest that education-based interventions are effective in encouraging community participation and behavioral change toward sustainable waste management. This program is expected to initiate long-term ecological awareness and inspire independent waste management practices at the household and community levels. Therefore, the activity serves as both a preventive and practical model for organic waste management in local environments.